PERANAN KOPERASI SIMPAN PINJAM PEMBIAYAAN SYARIAH BMT (KSPPS BMT) DALAM MENDUKUNG PERMODALAN USAHA MIKRO KECIL DAN MENENGAH DI KELURAHAN BUKIT GADO-GADO KOTA PADANG - Cindi Prisilia; Yenni Jufri; Yull Hartono (Jurnal Public Administration, Business and Rural Develoment Planning, 2023)
The results of this study indicate that: 1) The role of sharia financing savings and loan coorperative (KSPPS BMT) in supporting capital for micro, small and medium enterprises in the Bukit Gado-Gado sub district is to improve the walfare of members, especially mocro, small and medium enterprises. But this role is not working properly. This is evidenced by the 11 people who received financing, 9 people entered the non current category and 2 people entered the current category. The reason is because the profits from the business they run are used to meet their daily needs. 2) The obstacles faced by sharia financing savings and loan coorperatives are the non performing of micro, small and medium business actors in paying installments. So that the performance of coorperatives in carrying out their roles as institutions that support capital for micro, small and medium enterprises is disrupted and the lack of socialization carried out by coorperatives to micro, small and medium enterprises. The suggestions for this research are as follows: 1) KSPPS BMT Bukit Gado-Gado needs to conduct socialization related to the benefits of getting access to capital from coorperatives to all mico, small and medium business actors so that they can increase the number of micro, small and medium business actors who become members of financing from coorperatives. KSPPS BMT Bukit Gado-Gado must improve services and form programs to attract micro, small and medium enterprises to become members of the coorperative. 2) Micro, small and medium business actors who take loans from coorperatives must have a high awareness of making installment